The immunomodulating effect of bifidobacteria is modified by the anticoagulant acenocoumarol - Assad, Sabrina (2023)
Bifidobacteria are health promoting microorganisms that can interact with drugs in the intestinal tract thus modifying the activation of immune cells and host homeostasis. To study the effect of acenocoumarol on the interaction between bifidobacteria and THP-1 cells or intestinal epithelial cells. Bifidobacterium bifidum CIDCA 5310 and B. adolescentis CIDCA 5317 were grown in MRS broth in anaerobic conditions. The experiments were done in the presence of acenocoumarol. FITC-labeled bacteria were incubated with THP1 cells differentiated with PMA (THP1-PMA), and phagocytosis and intracellular localization of bacteria were assessed by flow cytometry and confocal laser microscopy, respectively. Also, expression of macrophage surface molecules in THP1 and THP1-PMA cells was assessed by flow cytometry. By using the Caco-2 ccl20:luc reporter system innate immune response was analysed by determining luciferase expression induced by flagellin. Acenocoumarol decreased phagocytosis of bifidobacteria but intracellular routing was not modified. Also, anticoagulant reduced the expression of HLA-DR and CD64 induced by bifidobacteria in both THP1-PMA and THP1 cells. Instead, the decrease in the expression of CD206 and CD23 was dependent on differentiation status of THP1 cells. Acenocoumarol increased CCL20 expression and it was partially abrogated by strain CIDCA 5310. Presence of acenocoumarol modifies the interaction between bifidobacteria and eukaryotic cells thus suggesting that the expected modulation of immune response by probiotic foods can be different in persons under anticoagulant treatment.